Microhardness under strain. III. Microhardness behavior during stress-induced polymorphic transition in blends of poly(butylene terephthalate) and its block copolymers - Boneva, D.; Calleja, F. J. Baltá; Fakirov, S.; Apostolov, A. A.; Krumova, M. (Journal of applied polymer science, 1998)
The microhardness (H) technique was recently applied to poly(butylene terephthalate) (PBT) and its multiblock copolymer of poly(ether ester) (PEE) type for examination of the stress‐induced polymorphic transition. In the present study, these investigations are extended to blends of PBT and PEE. For this purpose, drawn and annealed with fixed ends at 170°C for 6 h in vacuum bristles of PBT–PEE, blends were characterized with respect to their microhardness at various stages of tensile deformation. H was measured under stress, with each step of deformation amounting 5%. The variation of H with strain (ε) shows 2 sharp stepwise decreasing values (by 40%). Each step is defined in a relatively narrow deformation (ε) range (2–5%) due to the stress‐induced α → β polymorphic transitions arising in PBT crystallites. The first polymorphic transition (at ε = 2–3%) is assigned to the PBT crystallites of the homopolymer (homoPBT). The second transition (at ε = 25%) is associated to those crystals within the PEE copolymer. From the observation of two distinct transitions, separated by a deformation interval of ε = 20% it is concluded that (1) homoPBT and the PBT segments from PEE crystallize separately (no cocrystallization takes place), and (2) the 2 species of PBT crystallites are subject to the external mechanical loading, not in a simultaneous manner, but in a two‐stage process. In the deformation range between the 2 transitions (ε = 2–3% and 25%), it is pointed out that conformational changes are induced through stretching, mainly in the amorphous regions. © 1998 John Wiley & Sons, Inc. J Appl Polym Sci 69: 2271–2276, 1998